Nilai-Nilai Filosofi Yang Terkandung Dalam Rumah Berarsitektur Majapahit Di Desa Sentonorejo Mojokerto - Natasha Bilqies Andriyani; I Wayan Arsana (Concept: Journal of Social Humanities and Education, 2023)
This research is based on the philosophical values ​​contained in the Majapahit architecture house in the village of Sentonorejo, Mojokerto. The aims of this research are: 1) To find out what symbols are contained in the Majapahit architectural house; 2) To find out the meaning of the philosophy contained in the symbol of the Majapahit architectural house. The method used in this research is qualitative method. Data collection techniques used are interviews, documentation, observation. The results of this study that the architecture of the Majapahit house is part of the building using pressed red bricks. The meanings in the symbols of the Majapahit architectural house in the village of Sentonorejo, Mojokerto include ridge (the existence of a person's belief in the house), ukel (the crown or in the Javanese language has the philosophical meaning of an oversized hat), bricks (contained in a stone). brick is part of the sacred building material).